2011
DOI: 10.1029/2010jd015231
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of dry and wet deposition using tissue N contents and15N natural abundance in epilithic mosses in atmospheric NHy-dominated areas

Abstract: Measurement of dry N deposition by physical methods is time‐consuming because it is usually difficult to measure directly. In this study, an alternative approach has successfully been proposed by coupling isotopic ratios with tissue N contents of epilithic mosses. The method is to use moss N contents to quantitatively estimate total N (TN) deposition and then to use 15N natural abundance in mosses to discriminate dry and wet deposition in atmospheric NHy‐dominated areas (NHy/TN > 0.75). On the basis of the iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
(96 reference statements)
1
11
0
Order By: Relevance
“…Thus, studies have shown that moss δ 15 N is an ideal integrator of site‐specific information of N deposition (Stewart et al, 2002) and mosses can keep original N contents and δ 15 N values during decades of storage (Peñuelas & Filella, 2001; Pitcairn et al, 1995). In the 2000s, moss monitoring networks were first established in Western Europe (Harmens et al, 2014), after which moss N contents have been widely used to quantify N deposition fluxes in Europe (Bragazza et al, 2005; Gerdol et al, 2014), South Africa (Wilson et al, 2008), and China (Qu et al, 2016; Xiao & Liu, 2011). However, very few moss studies have been conducted on temporal variations of regional N deposition (Delgado et al, 2013; Peñuelas & Filella, 2001; Solga et al, 2006; Wilson et al, 2008), with few studies in East Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, studies have shown that moss δ 15 N is an ideal integrator of site‐specific information of N deposition (Stewart et al, 2002) and mosses can keep original N contents and δ 15 N values during decades of storage (Peñuelas & Filella, 2001; Pitcairn et al, 1995). In the 2000s, moss monitoring networks were first established in Western Europe (Harmens et al, 2014), after which moss N contents have been widely used to quantify N deposition fluxes in Europe (Bragazza et al, 2005; Gerdol et al, 2014), South Africa (Wilson et al, 2008), and China (Qu et al, 2016; Xiao & Liu, 2011). However, very few moss studies have been conducted on temporal variations of regional N deposition (Delgado et al, 2013; Peñuelas & Filella, 2001; Solga et al, 2006; Wilson et al, 2008), with few studies in East Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the δ 15 N analysis of mosses can reveal dominant N sources and or N preferences in N assimilation. In studies in China, for example, the δ 15 N of mosses on bare rock showed low values in regions where inorganic N deposition was dominated by NH4 + (Liu et al ., ; Xiao & Liu, ). However, the extent to which mosses rely on NH4 + and the extent to which they use NO3 and DON remain open questions.…”
Section: Introductionmentioning
confidence: 99%
“…Second, moss N bulk and δ 15 N bulk enable the high-resolution monitoring of anthropogenic N distribution at geographic scales that are difficult to achieve through direct sampling of the atmosphere. On the basis of the generally higher δ 15 N of NO 3 – than RDN in deposition, , moss N bulk and δ 15 N bulk were applicable to differentiate the dominant N form in deposition, facilitating a link between inputs of specific N species with ecosystem responses. Because N deposition in most regions of Europe and eastern Asia has a higher RDN than NO 3 – –N deposition, , a general pattern of decreasing moss δ 15 N bulk with an increasing ratio of RDN or NH 4 + –N to NO 3 – –N has been established. ,,, Such a relation is now extended to evaluate N deposition in eastern Asia, where RDN is markedly higher than NO 3 – –N in deposition (e.g., NH 4 + –N/NO 3 – –N = 3.1–21.5 in China). , …”
Section: Introductionmentioning
confidence: 99%